Serotonin Augments Gut Pacemaker Activity via 5-HT3 Receptors - Liu, Hong-Nian; Ohya, Susumu; Nishizawa, Yuji; Sawamura, Kenta; Iino, Satoshi; Syed, Mohsin Md; Goto, Kazunori; Imaizumi, Yuji; Nakayama, Shinsuke (PLOS ONE, 2011)
Serotonin (5-hydroxytryptamine: 5-HT) affects numerous functions in the gut, such as secretion, muscle contraction, and enteric nervous activity, and therefore to clarify details of 5-HT's actions leads to good therapeutic strategies for gut functional disorders. The role of interstitial cells of Cajal (ICC), as pacemaker cells, has been recognised relatively recently. We thus investigated 5-HT actions on ICC pacemaker activity. Muscle preparations with myenteric plexus were isolated from the murine ileum. Spatio-temporal measurements of intracellular Ca2+ and electric activities in ICC were performed by employing fluorescent Ca2+ imaging and microelectrode array (MEA) systems, respectively. Dihydropyridine (DHP) Ca2+ antagonists and tetrodotoxin (TTX) were applied to suppress smooth muscle and nerve activities, respectively. 5-HT significantly enhanced spontaneous Ca2+ oscillations that are considered to underlie electric pacemaker activity in ICC. LY-278584, a 5-HT3 receptor antagonist suppressed spontaneous Ca2+ activity in ICC, while 2-methylserotonin (2-Me-5-HT), a 5-HT3 receptor agonist, restored it. GR113808, a selective antagonist for 5-HT4, and O-methyl-5-HT (O-Me-5-HT), a non-selective 5-HT receptor agonist lacking affinity for 5-HT3 receptors, had little effect on ICC Ca2+ activity. In MEA measurements of ICC electric activity, 5-HT and 2-Me-5-HT caused excitatory effects. RT-PCR and immunostaining confirmed expression of 5-HT3 receptors in ICC. The results indicate that 5-HT augments ICC pacemaker activity via 5-HT3 receptors. ICC appear to be a promising target for treatment of functional motility disorders of the gut, for example, irritable bowel syndrome.